Selected writings and speeches of Alexander Hamilton - Hamilton, Alexander; Frisch, Morton J. (Washington : American Enterprise Institute for Public Policy Research, 1985)
The great American founding father speaks from the past in his own voice through 170 letters, speeches, essays, reports, and other documents.
Includes index.
Includes bibliographical references: p. 15-17.
aia 18/05/2018
Keywords: Politics and Government; Politics and Government -- Revolution; Addresses, essays, lectures; United States